Transcriptomic Analysis of the Differences in Leaf Color Formation during Stage Transitions in Populus × euramericana ‘Zhonghuahongye’ - Mengjiao Chen; Hui Li; Wan Zhang; Lin Huang; Jingle Zhu (Agronomy, 2022)
To explore the mechanism underlying the leaf color variation of Populus × euramericana ‘Zhonghuahongye’ (‘Zhonghong’ poplar) leaves at different maturation stages, we used ‘Zhonghong’ poplar leaves and analyzed the L* (lightness), a* (redness), and b* (yellowness) color difference values and the pigment contents in the three maturation stages. The Illumina HiSeqTM 2000 high−throughput sequencing platform was used for transcriptome sequencing analysis, and leaf color changes during stage transitions were preliminarily explored. Overall, with the increase in L* and b* during leaf development, the a*, C* (colour saturation), and chromatic values decreased, the total anthocyanin content decreased, and the chlorophyll and carotenoid content increased. A total of 11,868 differentially expressed genes were identified by transcriptome sequencing. Comparing the expression differences of structural genes involved in anthocyanin synthesis in the leaves at different stages, we identified 5612 genes in the R1 vs. R2 comparison, 10,083 in the R1 vs. R3 comparison, and 6068 in the R2 vs. R3 comparison (R1, R2, R3 refer to samples obtained on 1 April, 6 April, and 11 April, respectively). Key genes such as DFR (Dihydroflavanol 4−reductase), ANS (anthocyanidin synthase), FLS(flavonol synthase) , CHS(chalcone synthase), BZ1(Bronze 1), bHLH35, and bHLH63 were identified. These structural genes and those that encode transcription factors may be related to the regulation of anthocyanin synthesis. Here, the key genes related to leaf color change in ‘Zhonghong’ poplar were discovered, providing an important genetic basis for the subsequent genetic improvement of ‘Zhonghong’ poplar.